Classical mechanics : a computational approach with examples using mathematica and Python - Kulp, Christopher W.; Pagonis, Vasilis (Boca Raton, FL : CRC Press, 2021)
Classical Mechanics: A Computational Approach with Examples using Python and Mathematica provides a unique, contemporary introduction to classical mechanics, with a focus on computational methods. In addition to providing clear and thorough coverage of key topics, this textbook includes integrated instructions and treatments of computation. Full of pedagogy, it contains both analytical and computational example problems within the body of each chapter. The example problems teach readers both analytical methods and how to use computer algebra systems and computer programming to solve problems in classical mechanics. End-of-chapter problems allow students to hone their skills in problem solving with and without the use of a computer. The methods presented in this book can then be used by students when solving problems in other fields both within and outside of physics. It is an ideal textbook for undergraduate students in physics, mathematics, and engineering studying classical mechanics. Features: Gives readers the "big picture" of classical mechanics and the importance of computation in the solution of problems in physics Numerous example problems using both analytical and computational methods, as well as explanations as to how and why specific techniques were used Online resources containing specific example codes to help students learn computational methods and write their own algorithms A solutions manual is available via the Routledge Instructor Hub and extra code is available via the Support Material tab
5.1 WORK AND ENERGY IN ONE-DIMENSIONAL SYSTEMS -- 5.2 POTENTIAL ENERGY AND EQUILIBRIUM POINTS IN ONE-DIMENSIONAL SYSTEMS -- 5.3 WORK AND LINE INTEGRALS -- 5.4 THE WORK-KINETIC ENERGY THEOREM, REVISITED -- 5.5 CONSERVATIVE FORCES AND POTENTIAL ENERGY -- 5.6 ENERGY AND MULTIPARTICLE SYSTEMS -- 5.7 CHAPTER SUMMARY -- 5.8 END-OF-CHAPTER PROBLEMS -- Chapter 6: Harmonic Oscillations -- 6.1 DIFFERENTIAL EQUATIONS -- 6.2 THE SIMPLE HARMONIC OSCILLATOR -- 6.2.1 The Equation of Motion of the Simple Harmonic Oscillator -- 6.2.2 Potential and Kinetic Energy in Simple Harmonic Motion
Chapter 1. Foundations of Motion and Computation Chapter 2. Single-Particle Motion in One Dimesnison Chapter 3.Motion in Two and Three Dimensions Chapter 4. Momentum, Angular Momentum, and Multi-Particle Chapter 5. Energy Chapter 6. Harmonic Oscillations Chapter 7. The Calculus of Variations Chapter 8. Lagrangian and Hamiltonian Dynamics Chapter 9. Central Forces and Planetry Motions Chapter 10. Motion in Non-Inertial Reference Frames Chapter 11. Rigid Body Motion Chapter 12. Coupled Oscillations Chapter 13. Nonlinear Systems.
OCLC-licensed vendor bibliographic record.
Keywords: Python (Computer program language); Mathematica (Computer file); Mechanics; Mechanics -- Data processing; SCIENCE / Mathematical Physics; MATHEMATICS / Arithmetic